Low-loss CaMgSiO4-based microwave dielectric ceramic material and preparation method thereof

By introducing raw materials such as MgO, CaCO3 and other materials into CaMgSiO4-based microwave dielectric ceramic materials, and using composite modifiers of LiF and TiO2, the Li-Ti binary phase is pre-synthesized, which solves the problems of high dielectric loss and high sintering temperature of existing materials, and realizes the preparation of ceramic materials with low loss and low sintering temperature, which is suitable for microwave devices.

CN119797902AActive Publication Date: 2025-04-11CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510301141.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-11
Estimated Expiration
2045-03-14

AI Technical Summary

Technical Problem

The existing CaMgSiO4-based microwave dielectric ceramic materials have high dielectric loss, excessive resonance frequency temperature coefficient, and high sintering temperature, which limits their application in microwave devices.

Method used

By selecting minerals such as black talc and wollastonite as the main raw materials, and introducing raw materials such as MgO and CaCO3, combined with composite modifiers of LiF and TiO2, low-loss CaMgSiO4-based microwave dielectric ceramic materials were prepared by pre-synthesizing of Li-Ti binary phases. This method not only reduces the sintering temperature of the material, but also improves its resonant frequency temperature coefficient.

Benefits of technology

CaMgSiO4-based microwave dielectric ceramic material with low dielectric constant, low loss and low sintering temperature has excellent microwave dielectric properties and small resonant frequency temperature coefficient, and is suitable for microwave devices for millimeter wave communication.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797902A_ABST
    Figure CN119797902A_ABST
Patent Text Reader

Abstract

The invention discloses a low-loss CaMgSiO4-based microwave dielectric ceramic material and a preparation method thereof. The microwave dielectric ceramic material is prepared by sintering the following raw materials in parts by weight: 165 to 172 parts of black talc, 154 to 164 parts of wollastonite, 82 to 88 parts of MgO, 204 to 210 parts of CaCO3, 3 to 6 parts of LiF and 2 to 4 parts of TiO2. The preparation method comprises the following steps: crushing, grinding and sieving black talc and wollastonite ore to obtain black talc and wollastonite ore powder; liF and TiO2 are weighed, mixed and calcined; the preparation method comprises the following steps: weighing black talc, wollastonite, MgO and CaCO3 powder in proportion, and carrying out wet ball milling and mixing; carrying out drying, calcining, heat preservation and furnace cooling on the ball-milled powder; powder obtained by calcination and a composite modifier are uniformly mixed through dry barreling; sintering is performed after blank making. The CaMgSiO4 ceramic material prepared by the preparation method disclosed by the invention has ultralow dielectric loss and a relatively small temperature coefficient of resonance frequency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a ceramic material and a method for making the same, and is specifically a low-loss CaMgSiO 4 Based microwave dielectric ceramic material and preparation method thereof. Background Art

[0002] Microwave dielectric ceramic materials are widely used in microwave devices such as resonators, filters, and dielectric antennas. With the increasing perfection of 5G communication technology, the demand for low-cost, high-frequency, and lightweight microwave devices in mobile, satellite communications, and wireless local area networks (WLAN) is increasing, which requires microwave dielectric ceramic materials to have low cost, low density, and excellent microwave dielectric properties (low εr , to avoid signal delay; high Q×f , to ensure excellent frequency selection characteristics; near zero τf , to ensure high thermal stability).

[0003] In recent years, with the rapid progress of microwave communication and radar technology, many applicable microwave ceramics generally have high εr ( εr >10) and Q×f , for example: Y 2 ba 0.4 Ni 0.6 O 5 ,Mg 4 Nb 2 O 9 , LaBO 3 ,Ba(Zn 1 / 3 Ta 2 / 3 ) 3 However, the large relative dielectric constant ( εr >10) limits their application in microwave dielectric resonators. The high relative dielectric constant increases the exchange coupling loss between it and the electrode, thereby reducing the transmission rate of electrical signals. Researchers have found that CaMgSiO 4 Microwave dielectric ceramic material is a low dielectric constant ceramic material with great application potential. However, its high dielectric loss and high resonant frequency temperature coefficient limit its further application.

[0004] Therefore, how to further reduce CaMgSiO 4 The dielectric loss of the ceramic system effectively adjusts the τ f value, lowering its sintering temperature has become a key technical issue that needs to be solved urgently. Summary of the invention

[0005] Purpose of the invention: In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a low-loss CaMgSiO 4 Another object of the present invention is to provide a low sintering temperature, low loss CaMgSiO 4 Preparation method of microwave dielectric ceramic material.

[0006] Technical solution: A low-loss CaMgSiO 4 The microwave dielectric ceramic material is prepared by sintering the following raw materials in parts by weight: 165-172 parts of black talc, 154-164 parts of wollastonite, 82-88 parts of MgO, 204-210 parts of CaCO 3 , 3~6 parts LiF, 2~4 parts TiO 2 .

[0007] Furthermore, low-loss CaMgSiO 4 The main phase of the microwave dielectric ceramic material is CaMgSiO 4 .

[0008] Furthermore, low-loss CaMgSiO 4 The relative dielectric constant of the base microwave dielectric ceramic material is 7.85~8.39, the quality factor is 95537~116916GHz, and the resonant frequency temperature coefficient is -26~ -30ppm / ℃.

[0009] The above low loss CaMgSiO 4 The method for preparing a microwave dielectric ceramic material comprises the following steps:

[0010] Step S1, crushing and grinding black talc and wollastonite ores respectively, and sieving them to obtain black talc and wollastonite ore powders;

[0011] Step S2: weigh LiF and TiO in proportion 2 Powder, grind and mix and then calcine;

[0012] Step S3: weigh black talc powder, wollastonite powder, MgO, CaCO in proportion. 3 , wet ball milling mixing;

[0013] Step S4, drying, calcining, heat preservation, and cooling with the furnace;

[0014] Step S5, adding the product obtained in step S2 to the product obtained in step S4, and dry rolling and mixing;

[0015] Step S6: Take out the powder obtained in step S5, prepare a blank from the powder and then sinter it to obtain low-loss CaMgSiO 4 Based microwave dielectric ceramic materials.

[0016] Furthermore, in step S1, the particle size of the black talc and wollastonite after crushing, grinding and screening is 38-75 μm.

[0017] Further, in step S2, LiF and TiO 2 The powders are all analytically pure, the grinding time is 15~30min, the calcination temperature is 550~700℃, and the insulation time is 2~4h.

[0018] Further, in step S3, MgO and CaCO 3 The powders are all analytically pure, the ball milling is wet ball milling, the ball milling speed is 200~250r / min, and the ball milling time is 8~12h. Wet ball milling makes the material easier to grind, improves the grinding efficiency, and improves the uniformity of the material.

[0019] Furthermore, in step S4, the calcination temperature is 900-1000°C and the holding time is 2-4h. If the calcination temperature is lower than 900°C, the powder contains the raw material phase, and the impurity phase is likely to appear in the subsequent sintering process; if the calcination temperature is higher than 1000°C, the powder particle size becomes larger, and the reaction activity becomes worse in the subsequent sintering process.

[0020] Furthermore, in step S5, the ball milling is dry rolling milling, the ball milling speed is 180-220 r / min, and the ball milling time is 16-24 hours. Dry rolling milling can prevent the separation of the main material and the composite modifier in the aqueous grinding medium, so that the composite modifier can be evenly dispersed in the main material.

[0021] Furthermore, in step S6, the sintering temperature is 1100-1200°C, and the temperature is kept for 4-6 hours after sintering, and then cooled with the furnace. If the sintering temperature is lower than 1000°C, the sintering power of the ceramic material is insufficient, the density is reduced, and the performance is reduced; if the sintering temperature is higher than 1200°C, the ceramic grains grow abnormally, and the grains are coated during the grain growth process, resulting in an increase in porosity, a decrease in density, and a decrease in performance.

[0022] Preparation principle: MgO, CaCO 3 The raw materials are introduced into black talc and wollastonite, which makes up for the problem of insufficient Mg and Ca in the mineral material composition, thus ensuring that the main crystal phase of the final ceramic product is CaMgSiO 4 , thereby greatly reducing the dielectric loss of the material, LiF and TiO 2 The powder is pre-synthesized into Li-Ti binary phase by high temperature calcination, so that the composite modifier contains TiO 2 The Li-Ti binary phase not only reduces the sintering temperature of the material, but also improves the resonant frequency temperature coefficient τ of the ceramic material. f .

[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0024] 1. Using wollastonite and black talc as the main raw materials, low-cost CaMgSiO 4 Base microwave dielectric ceramic materials;

[0025] 2. Choose LiF and TiO 2 The composite modifier, through the preparation method of pre-synthesizing Li-Ti binary phase, reduces the sintering temperature of the material and improves the resonant frequency temperature coefficient of the material without reducing the quality factor (Q×f) of the ceramic material;

[0026] 3. It has ultra-low dielectric loss and a small resonant frequency temperature coefficient, and mineral raw materials account for more than half of the usage, providing a low-cost solution for microwave devices and materials for millimeter wave communications. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The low-loss CaMgSiO prepared in Example 2 of the present invention 4 XRD pattern of based microwave dielectric ceramic materials.

[0028] Figure 2 The low-loss CaMgSiO prepared in Example 2 of the present invention 4 SEM image of the base microwave dielectric ceramic material.

[0029] Figure 3 The low-loss CaMgSiO prepared in Comparative Example 1 of the present invention 4 SEM image of the base microwave dielectric ceramic material. DETAILED DESCRIPTION

[0030] The materials, reagents, instruments, etc. used in the following examples are all commercially available unless otherwise specified. The experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The specific compositions of black talc powder and wollastonite are shown in Table 1.

[0031] Table 1 Elemental composition of black talc powder and wollastonite ore (%)

[0032]

[0033] Example 1

[0034] A low-loss CaMgSiO 4 The method for preparing a microwave dielectric ceramic material comprises the following steps:

[0035] Step S1, crushing black talc and wollastonite ore respectively, grinding and sieving them to make the average particle size of black talc and wollastonite ore powder be 45 μm.

[0036] Step S2: weigh 0.3 g LiF powder and TiO 2 0.3 g of powder was used. The two weighed powders were manually ground and mixed for 15 min. The mixed powders were placed in a muffle furnace and calcined at 550 °C and kept warm for 2 h, and then cooled with the furnace.

[0037] Step S3: weigh 16.5 g black talc powder, 15.4 g wollastonite powder, 8.2 g MgO powder, and CaCO 3 20.4 g of powder was wet-milled at 200 r / min for 8 h and dried.

[0038] Step S4: calcine the product obtained in step S3 in a muffle furnace at 900° C. and keep the temperature for 2 hours, and cool it with the furnace.

[0039] Step S5, the calcined powders of step S2 and step S4 are mixed and dry-milled at a speed of 180 r / min for 16 h.

[0040] Step S6: Take out the powder obtained in step S5, press the green body and place it in a high-temperature muffle furnace for sintering at a temperature of 1150°C for 4 hours, and then cool it in the furnace to obtain low-loss CaMgSiO 4 Based microwave dielectric ceramic materials.

[0041] Example 2

[0042] A low-loss CaMgSiO 4 The method for preparing a microwave dielectric ceramic material comprises the following steps:

[0043] Step S1, crushing black talc and wollastonite ore respectively, grinding and sieving them to make the average particle size of black talc and wollastonite ore powder be 45 μm.

[0044] Step S2: weigh 0.6 g LiF powder and TiO 2 0.3g of powder was used. The two weighed powders were manually ground and mixed for 20min. The mixed powders were placed in a muffle furnace and calcined at 600℃ and kept warm for 2h, and then cooled with the furnace.

[0045] Step S3: weigh 16.9 g black talc powder, 15.8 g wollastonite powder, 8.6 g MgO powder, and CaCO 3 20.8 g of powder was wet-milled at a rotation speed of 225 r / min for 9 h and dried.

[0046] Step S4, placing the product obtained in step S3 in a muffle furnace for calcination at 950° C. and keeping the temperature for 4 hours, and cooling with the furnace.

[0047] Step S5, the calcined powders of step S2 and step S4 are mixed and dry-milled at a speed of 190 r / min for 18 h.

[0048] Step S6: Take out the powder obtained in step S5, press the green body and place it in a high-temperature muffle furnace for sintering at a temperature of 1100°C for 6 hours, and then cool it in the furnace to obtain low-loss CaMgSiO 4 Based microwave dielectric ceramic materials.

[0049] Example 3

[0050] A low-loss CaMgSiO 4 The method for preparing a microwave dielectric ceramic material comprises the following steps:

[0051] Step S1, crushing black talc and wollastonite ore respectively, grinding and sieving them to make the average particle size of black talc and wollastonite ore powder be 45 μm.

[0052] Step S2: weigh 0.5 g LiF powder and TiO 2 0.4 g of powder was used. The two weighed powders were manually ground and mixed for 25 min. The mixed powders were placed in a muffle furnace and calcined at 650 °C and kept warm for 4 h, and then cooled with the furnace.

[0053] Step S3: weigh 17.2 g of black talc powder, 16.2 g of wollastonite powder, 8.8 g of MgO powder, and 1.5 g of CaCO 3 20.6 g of powder was wet-milled at 250 r / min for 10 h and dried.

[0054] Step S4, placing the product obtained in step S3 in a muffle furnace for calcination at 1000° C. and keeping the temperature for 3 hours, and cooling with the furnace.

[0055] Step S5, mixing the calcined powders from step S2 and step S4 and dry-milling them at a speed of 200 r / min for 20 h.

[0056] Step S6: Take out the powder obtained in step S5, press the green body and place it in a high-temperature muffle furnace for sintering at a temperature of 1200°C for 5 hours, and then cool it in the furnace to obtain low-loss CaMgSiO 4 Based microwave dielectric ceramic materials.

[0057] Example 4

[0058] A low-loss CaMgSiO 4 The method for preparing a microwave dielectric ceramic material comprises the following steps:

[0059] Step S1, crushing black talc and wollastonite ore respectively, grinding and sieving them to make the average particle size of black talc and wollastonite ore powder be 45 μm.

[0060] Step S2: weigh 0.4 g LiF powder and TiO 2 0.2g of powder was used. The two weighed powders were manually ground and mixed for 30min. The mixed powders were placed in a muffle furnace and calcined at 700℃ and kept warm for 3h, and then cooled with the furnace.

[0061] Step S3: weigh 17.0 g black talc powder, 16.4 g wollastonite powder, 8.4 g MgO powder, and CaCO 3 21.0 g of powder was wet-milled at a rotation speed of 225 r / min for 11 h and dried.

[0062] Step S4, placing the product obtained in step S3 in a muffle furnace for calcination at 950° C. and keeping the temperature for 4 hours, and cooling with the furnace.

[0063] Step S5, the calcined powders from step S2 and step S4 are mixed and dry-milled at a speed of 210 r / min for 22 h.

[0064] Step S6: Take out the powder obtained in step S5, press the green body and place it in a high-temperature muffle furnace for sintering at a sintering temperature of 1100°C for 5 hours, and then cool it in the furnace to obtain low-loss CaMgSiO 4 Based microwave dielectric ceramic materials.

[0065] Example 5

[0066] A low-loss CaMgSiO 4 The method for preparing a microwave dielectric ceramic material comprises the following steps:

[0067] Step S1, crushing black talc and wollastonite ore respectively, grinding and sieving them to make the average particle size of black talc and wollastonite ore powder be 45 μm.

[0068] Step S2: weigh 0.6 g LiF powder and TiO 2 0.4 g of powder was used. The two weighed powders were manually ground and mixed for 20 min. The mixed powders were placed in a muffle furnace and calcined at 600 °C and kept warm for 4 h, and then cooled with the furnace.

[0069] Step S3: weigh 16.7 g black talc powder, 15.6 g wollastonite powder, 8.6 g MgO powder, and CaCO 3 20.6 g of powder was wet-milled at 200 r / min for 12 h and dried.

[0070] Step S4, placing the product obtained in step S3 in a muffle furnace for calcination at 900° C. and keeping the temperature for 3 hours, and cooling with the furnace.

[0071] Step S5, the calcined powders of step S2 and step S4 are mixed and dry-milled at a speed of 220 r / min for 24 h.

[0072] Step S6: Take out the powder obtained in step S5, press the green body and place it in a high-temperature muffle furnace for sintering at a temperature of 1150°C for 4 hours, and then cool it in the furnace to obtain low-loss CaMgSiO 4 Based microwave dielectric ceramic materials.

[0073] Comparative Example 1

[0074] The black talc and wollastonite were crushed, ground and sieved respectively to make the average particle size of the black talc and wollastonite powders 45 μm. Take 16.9 g of black talc powder, 15.8 g of wollastonite powder, 8.6 g of MgO powder, and CaCO 3 20.8g of powder was wet ball milled at 225r / min for 9h. After drying, the powder was placed in a muffle furnace for calcination at 950℃ and kept warm for 4h, and then cooled with the furnace. The calcined powder was dry rolled at 190r / min for 18h. After rolling, the powder was pressed and sintered in a high-temperature muffle furnace at 1400℃ for 6h, and then cooled with the furnace to obtain low-loss CaMgSiO 4 Based microwave dielectric ceramic materials.

[0075] Comparative Example 2

[0076] The black talc and wollastonite were crushed, ground and sieved respectively to make the average particle size of the black talc and wollastonite powders 45 μm. Take 16.9 g of black talc powder, 15.8 g of wollastonite powder, 8.6 g of MgO powder, and CaCO 3 20.8g of powder was wet ball milled at a speed of 225r / min for 9h. After drying, the powder was placed in a muffle furnace for calcination at 950℃ and kept warm for 4h, and then cooled with the furnace. 0.6g of LiF powder was added to the calcined powder, and dry rolling was carried out at a speed of 190r / min for 18h. After rolling, the powder was pressed and sintered in a high-temperature muffle furnace at a sintering temperature of 1350℃ for 6h, and then cooled with the furnace to obtain low-loss CaMgSiO 4 Based microwave dielectric ceramic materials.

[0077] Comparative Example 3

[0078] The black talc and wollastonite were crushed, ground and sieved respectively to make the average particle size of the black talc and wollastonite powders 45 μm. Take 16.9 g of black talc powder, 15.8 g of wollastonite powder, 8.6 g of MgO powder, and CaCO 3 20.8g of powder was wet-milled at 225r / min for 9h. After drying, the powder was placed in a muffle furnace and calcined at 950℃ for 4h and then cooled. 0.3g TiO was added to the calcined powder. 2The powder was dry-milled at a speed of 190 r / min for 18 h. After milling, the powder was pressed into a green compact and sintered in a high-temperature muffle furnace at a sintering temperature of 1450 ° C for 6 h. The powder was then cooled with the furnace to obtain low-loss CaMgSiO 4 Based microwave dielectric ceramic materials.

[0079] Comparative Example 4

[0080] The black talc and wollastonite were crushed, ground and sieved respectively to make the average particle size of the black talc and wollastonite powders 45 μm. Take 16.9 g of black talc powder, 15.8 g of wollastonite powder, 8.6 g of MgO powder, and CaCO 3 20.8g of powder was wet-milled at 225r / min for 9h. After drying, the powder was placed in a muffle furnace and calcined at 950℃ for 4h and then cooled. 0.6g LiF and 0.3g TiO were added to the calcined powder. 2 The powder was dry-milled at a speed of 190 r / min for 18 h. After milling, the powder was pressed into a green compact and sintered in a high-temperature muffle furnace at a sintering temperature of 1300 ° C for 6 h. The powder was then cooled in the furnace to obtain low-loss CaMgSiO 4 Based microwave dielectric ceramic materials.

[0081] Table 2 Properties of materials obtained in various embodiments and comparative examples

[0082]

[0083] Table 1 shows that Examples 1 to 5 are low-loss CaMgSiO 4 The microwave dielectric properties and sintering properties of the base ceramic materials under different formulations and process conditions. Among them, the ceramic sample prepared in Example 2 has the lowest relative dielectric constant, the highest quality factor, the smallest absolute value of the resonant frequency temperature coefficient, and the lowest sintering temperature, which is the optimal embodiment. Figure 1 As shown, the main phase is CaMgSiO 4 Compared with Example 2, Comparative Example 1 prepared a 2 Ceramic samples such as Figure 2 (Example 2) and Figure 3 As shown in (Comparative Example 1), the ceramic material prepared in Comparative Example 1 has poor density and more pores, so the dielectric properties and sintering properties are poor. 2 The resonant frequency temperature coefficient of the ceramic sample was not improved. In Comparative Example 3, a ceramic sample without adding LiF was prepared, and the sintering performance was relatively poor. 2Two modifiers are used, but the Li-Ti binary phase is not pre-synthesized by high-temperature calcination. Therefore, compared with Example 2, the dielectric properties and sintering properties are generally lower.

Claims

1. A low-loss CaMgSiO4-based microwave dielectric ceramic material, characterized in that: It is prepared by sintering the following raw materials in parts by weight: 165-172 parts of black talc, 154-164 parts of wollastonite, 82-88 parts of MgO, 204-210 parts of CaCO3, 3-6 parts of LiF, and 2-4 parts of TiO2.

2. The low-loss CaMgSiO4-based microwave dielectric ceramic material according to claim 1, characterized in that: Its main phase is CaMgSiO4.

3. The low-loss CaMgSiO4-based microwave dielectric ceramic material according to claim 1, characterized in that: The low-loss CaMgSiO4-based microwave dielectric ceramic material has a relative dielectric constant of 7.85 to 8.39, a quality factor of 95537 to 116916 GHz, and a resonant frequency temperature coefficient of -26 to -30 ppm / °C.

4. A method for preparing a low-loss CaMgSiO4-based microwave dielectric ceramic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step S1, crushing black talc and wollastonite respectively, grinding and sieving to obtain black talc ore powder and wollastonite ore powder; Step S2, weighing LiF and TiO2 powders in proportion, grinding and mixing, and then calcining; Step S3, weighing black talc powder, wollastonite powder, MgO and CaCO3 in proportion, and mixing by wet ball milling; Step S4, drying, calcining, heat preservation, and cooling with the furnace; Step S5, adding the product obtained in step S2 to the product obtained in step S4, and dry rolling and mixing; Step S6, taking out the powder obtained in step S5, preparing a blank from the powder and then sintering it to obtain a low-loss CaMgSiO4-based microwave dielectric ceramic material.

5. The method for preparing a low-loss CaMgSiO4-based microwave dielectric ceramic material according to claim 4, characterized in that: In the step S1, the particle size of the black talc and wollastonite after crushing, grinding and screening is 38-75 μm.

6. The method for preparing a low-loss CaMgSiO4-based microwave dielectric ceramic material according to claim 4, characterized in that: In the step S2, LiF and TiO2 powders are both analytically pure, the grinding time is 15-30 min, the calcination temperature is 550-700° C., and the ball milling time is 2-4 h.

7. The method for preparing a low-loss CaMgSiO4-based microwave dielectric ceramic material according to claim 4, characterized in that: In the step S3, the MgO and CaCO3 powders are both analytically pure, the ball milling is wet ball milling, the ball milling speed is 200-250 r / min, and the ball milling time is 8-12 h.

8. The method for preparing a low-loss CaMgSiO4-based microwave dielectric ceramic material according to claim 4, characterized in that: In step S4, the calcination temperature is 900-1000° C., and the holding time is 2-4 hours.

9. The method for preparing a low-loss CaMgSiO4-based microwave dielectric ceramic material according to claim 4, characterized in that: In step S5, the ball milling is dry rolling milling, the ball milling speed is 180-220 r / min, and the ball milling time is 16-24 h.

10. The method for preparing a low-loss CaMgSiO4-based microwave dielectric ceramic material according to claim 4, characterized in that: In the step S6, the sintering temperature is 1100-1200° C., and the sintering temperature is kept for 4-6 hours, followed by cooling in the furnace.

Citation Information

Patent Citations

  • Lithium-magnesium-titanium-based microwave dielectric ceramic with high Q value and low temperature sintering realization method thereof

    CN104844193A

  • Microwave dielectric ceramic material with low dielectric constant and preparation method thereof

    CN106587968A

  • Low-dielectric high-Q temperature-stable type perovskite structure LTCC microwave dielectric material and preparation method thereof

    CN110981440A

  • Black talc mineral microwave dielectric ceramic material and preparation method thereof

    CN115536377A

  • Li2.12MgTi3O8-based microwave dielectric ceramic material for LTCC (Low Temperature Co-Fired Ceramic) and preparation method thereof

    CN118388233A